2017
DOI: 10.7326/m16-1301
|View full text |Cite
|
Sign up to set email alerts
|

Physician Decision Making and Clinical Outcomes With Laboratory Polysomnography or Limited-Channel Sleep Studies for Obstructive Sleep Apnea

Abstract: National Health and Medical Research Council and Repat Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 33 publications
2
34
0
1
Order By: Relevance
“…It may be just as important to abolish snoring as well as improve the adverse health consequences associated with OSA (eg, reduced daytime sleepiness). It is worth noting that the surgical nonresponders had a significant reduction in ESS post surgery of two points, which is a clinically significant difference for the ESS, 36 this finding was observed in nonresponders regardless of the definition of success applied (see Supplementary material, Tables E5-E7).…”
Section: Limitationsmentioning
confidence: 80%
“…It may be just as important to abolish snoring as well as improve the adverse health consequences associated with OSA (eg, reduced daytime sleepiness). It is worth noting that the surgical nonresponders had a significant reduction in ESS post surgery of two points, which is a clinically significant difference for the ESS, 36 this finding was observed in nonresponders regardless of the definition of success applied (see Supplementary material, Tables E5-E7).…”
Section: Limitationsmentioning
confidence: 80%
“…The authors concluded that the proposed protocol could potentially offer a cost-effective tool to manage OSAS and expedite diagnosis particularly in rural and remote regions. In a recent study, Chai-Coetzer et al [53] analyzed the influence of abbreviated sleep studies on physician decision making and patient outcomes.…”
Section: Oximetry In Clinical Practicementioning
confidence: 99%
“…A recent study found no major changes in patient outcomes and physician confidence in the diagnoses when using cardiorespiratory polygraphy. Additionally, a significantly lower improvement in symptoms and CPAP compliance, as well as lower diagnostic confidence were reported when using pulse oximetry alone, primarily in milder cases [53]. Similarly, data supporting simplified monitoring 29 at home for the diagnosis of OSAS in children is currently insufficient.…”
Section: Oximetry Portable Monitoring By Means Of Smartphonesmentioning
confidence: 99%
“…Furthermore, as oxygen desaturation has been linked with adverse consequences associated with OSA (Bradley & Floras, ; Drager, Jun, & Polotsky, ; Ryan, Taylor, & Mcnicholas, ), detecting those with nocturnal hypoxaemia may be arguably more important than detecting those with apnoeas and hypopnoeas without significant oxygen desaturation. Nevertheless, physicians’ confidence in managing patients with OSA based solely on ODI 3% has been shown to be lower than when full polysomnographic data are available, despite the high diagnostic utility of ODI 3% (area under the receiver operating characteristic curve being 0.94 [95% CI 0.90–0.98]) and non‐inferior clinical improvement in patients treated based solely on ODI versus full polysomnography data (Chai‐Coetzer et al., ). This lack of confidence among the physicians may arise from inadequate prior experience in management models solely using ODI 3% data (cf.…”
Section: Discussionmentioning
confidence: 99%